ANALISIS KEANDALAN DALAM PERANCANGAN TEKNIK, STUDI KASUS SISTEM KENDALI ELEVATOR PESAWAT CN235-220 - Suweca, I Wayan; Sufyani, Rosyidin (Mesin, 2002)
This paper presents a reliability analysis of elevator control system for CN235-220 aircraft. The analysis is carried out using Bayes theorem. Reliability analysis is performed for several system configurations, existing system and two modified systems. Reliability calculation shows that one of the modified systems has reliability relatively higher than the existing system. To insure all requirement needed, the other analysis i.e. strength, stability, etc. must be conducted for the modified system.